Rurban Communities of Quito: Between the Entrepreneurialism and the Right to the City - Manuel Bayón Jiménez (Íconos)
Two seemingly contradictory spatial trends are occurring today in the peri-urban areas of Quito, which reshapes the dispute of territorialities: i) an unprecedented expansion of the urban area along the rural boroughs and ii) a growing recognition of land rights of indigenous and peasant communities in the Constitution of Ecuador, as well as the right to the city. This paper analyzes how both trends are related in the context of the largest infrastructure project in Quito in the last decade: the New Quito International Airport (NAIQ by its Spanish acronym). Tababela, the borough where NAIQ sits, was a predominantly rural area until the construction of the new airport. The operation of NAIQ is the embodiment of a very strong capital re-territorialization through an entrepreneurialism management of Quito that has materialized in the area through this Big Urban Project (GPU by its Spanish acronym). The processes of territorial appropriation by the populations affected by the NAIQ make it possible to analyze their response to this territorial model from a perspective on how the hegemony of power groups has operated in the urban public policies.